Qualitative properties and retrogradation of Buckwheat (Fagopyrum esculentum Moench) vegetable Jeolpyeon during storage - Lee, Yu-Na; Kim, Juyoung; Ha, Ae-Wha; Kim, Soo-Min; Hong, Wan-Su; Kim, Young-Soon (Progress in Nutrition, 2014)
Jeolpyeon is a type of Korean rice cake with health benefits, and buckwheat is a vegetable with multiple functional properties. The purpose of this study was to investigate the quality characteristics and retrogradation of Jeolpyeon made with buckwheat vegetable powder (BVP). The Jeolpyeon containing 2% BVP showed the best sensory properties such as taste, flavor, and overall preference. Treatments with added BVP had higher moisture content than that of the control group. Hardness, fracturability, and chewiness of all samples increased during the storage period. Generally, the greater the addition of BVP, the lower the increased rate of hardness. The 2% sample showed the slowest retrogradation as obtained by measurements using the Avrami equation. Thus, adding 2% buckwheat vegetable powder is recommended for desirable characteristics when preparing buckwheat vegetable Jeolpyeon.